Linear Parameter-Varying Versus Linear Time-Invariant Reduced-Order Controller Design for Turboprop Aircraft Dynamics - Widowati Widowati; Bambang Riyanto; Hari Muhammad (Institute for Research and Community Services, Institut Teknologi Bandung, 2012)
The applicability of parameter-varying reduced-order controllers to aircraft models is proposed. A generalization of the balanced singular perturbation method of the linear time-invariant (LTI) system was used to reduce the order of the linear parameter-varying (LPV) system. Based on the reducedorder model, a low-order LPV controller was designed using the Hâˆž synthesis technique. The performance of the reduced-order controller was examined by applying it to the lateral-directional control of a 20th-order aircraft model. Furthermore, the time responses of the closed-loop system with several reducedorder LPV controllers and a reduced-order LTI controller were compared. The simulation results show that an , 8th -order LPV controller can maintain stability and provide the same level of closed-loop system performance as a full-order LPV controller. This was not the case with the reduced-order LTI controller, which cannot maintain stability and performance for all allowable parameter trajectories.